William Faulkner : seeing through the South - Matthews, John T. (Chichester, U.K. ; Malden, MA : Wiley-Blackwell, 2009)
This succinct, yet comprehensive account of William Faulkner's literary career, novels, and key short stories offers an imaginative topography of his efforts to reckon with his Southern past, to acknowledge its modernization, and to develop his own modernist method.:.; Provides a brief but comprehensive account of Faulkner's literary career, through discussion of his novels and key short stories.; Offers an imaginative topography of Faulkner's efforts to reckon with his Southern past, to acknowledge its modernization, and to develop his own modernist method.; Draws on various specialized criti.
Seeing through the South: Faulkner and the life work of writing -- An artist never quite at home: Faulkner's apprehension of modern life -- That evening sun go down: the plantation South at twilight -- Come up: from red necks to riches -- The planting of men: the South and New World colonialism -- Seeing a South beyond Yoknapatawpha.
Includes bibliographical references (pages 296-301) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Faulkner, William, -- 1897-1962 -- Criticism and interpretation; Faulkner, William, -- 1897-1962.; Faulkner, William, -- 1897-1962.; Southern States -- In literature; Literature; Southern States; Electronic books; Criticism, interpretation, etc